GAMBARAN PENGETAHUAN DAN SIKAP ORANG TUA SISWA KELAS I DAN II SDN 005 BUKIT KAPUR DUMAI TENTANG KARIES GIGI - ", Noreba; Restuastuti, Tuti; Mammunah, Wan Fajriatul (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTCaries is a demineralization of the tooth surface caused by bacteria. Parents who have a low knowledge about the prevention of dental caries, tend to pay less attention to the oral health of children that can cause dental caries.The purpose of this study to describe the knowledge and attitudes of parents about dental caries. This research was conducted in SDN 005 Bukit Kapur Dumai descriptive with cross sectional approach. Samples in this study are the parents of the students of class I and II, and with a sample size of at least 150 parents. Data were collected by interview using a questionnaire. From the results of this study, scoring on a sufficient level of knowledge (54.67%), neutral position (62.00%). Based on gender the parents who followed in this study were (64.00%) of women with an age range of 20-35 years (60.00%) also had high school (56.00%) and work as a housewife (55, 33%).Keywords: Knowledge, attitudes, dental caries